The Effect of The Role of School Resources and School Performance on The Admission Strategy of New Students - Teddy Oswari; Siti Juariah (International Journal of Economics, Social Science, Entrepreneurship and Technology (IJESET), 2022)
This study aims to describe the role of school resources and school performance in order to create a strategy in increasing the acceptance of new students at private junior high schools in Bekasi district. The research approach used is a quantitative approach with case studies. The research instrument is human and non-human resources in the school. Collecting data using questionnaires to respondents. Respondents consisted of elements of the education office, foundation organs, all school members and parents/guardians of students. The analysis technique uses Multiple Linear Regression with SPSS version 25. The conclusion is that the role of the principal, the role of the teacher/educator, the principal's performance and the teacher's performance have a significant effect in influencing the strategy of accepting new students at Barhari Private Junior High School, Bekasi Regency or in other words accept H1.